Implementation of Eco-print Batik Steamer Machine to Optimize the Color Transfer Process in SME Fabric - Rahayu, Imami Arum Tri; Sari, Handini Novita; Anifah, Lilik; Budijono, Agung Prijo; Umaroh, Susi Tri (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Daun Efek is a Small Medium Enterprises in Sidoarjo which is engaged in the production of eco-print batik cloth. In making eco-print batik, UKM Daun Efek still uses conventional methods, thus causing the limited amount of production produced. Other constraints faced are the lack of attractive product packaging and lack of widespread marketing, so that turnover is difficult to increase due to lack of consumer reach. This activity uses an implementation method through a participatory approach, including such as FGDs, training and mentoring as well as discussion activities to exchange experiences between the proposing team and partners. From the implementation method that implemented, a grant machine was produced in the form of an eco-print batik steamer machine, which is able to increase the amount of production from 6 sheets of batik cloth per day to 18 pieces of batik cloth per day. In addition to production management, there was also improved the quality of product packaging from simple and unattractive to a packaging that has good, creative, and imprinted elements in the eyes of consumers through green box-shaped packaging with the partner logo. The reach of consumers has become wider with the marketing through social media.